2012
DOI: 10.2105/ajph.2011.300427
|View full text |Cite
|
Sign up to set email alerts
|

Potential Determinants of Coal Workers’ Pneumoconiosis, Advanced Pneumoconiosis, and Progressive Massive Fibrosis Among Underground Coal Miners in the United States, 2005–2009

Abstract: Enhanced surveillance results confirmed the persistence of severe CWP among US coal miners and documented the health consequences of inadequate dust control for miners in parts of Appalachia and at smaller mines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 8 publications
0
36
0
1
Order By: Relevance
“…Exposure to respirable crystalline silica dusts is very common in a multitude of industries and occupational settings. Inhalation of fine silica, including their most abundant naturally occurring polymorphs quartz and cristobalite, can lead to progressive pulmonary fibrosis and silicosis which continues to be a problem in developed and in third world countries [ 1 ]. The presence and severity of the disease depends on many factors such as individual susceptibility, and the level and duration of exposure [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to respirable crystalline silica dusts is very common in a multitude of industries and occupational settings. Inhalation of fine silica, including their most abundant naturally occurring polymorphs quartz and cristobalite, can lead to progressive pulmonary fibrosis and silicosis which continues to be a problem in developed and in third world countries [ 1 ]. The presence and severity of the disease depends on many factors such as individual susceptibility, and the level and duration of exposure [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…19 Further study is important given that the central Appalachian coal fields have been identified as an area with significant rates of rapidly progressive and advanced disease. 6,7,2527 …”
Section: Discussionmentioning
confidence: 99%
“…The average age of death due to pneumoconiosis significantly decreased from 2011 to 2012 in Kentucky then remained the same in 2013. This result may suggest that workers are being diagnosed with severe forms of pneumoconiosis at younger ages, and young miners with less mining tenure may be at heightened risk for the development of pneumoconiosis [Laney et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…There has not only been an increase in prevalence, but also in the severity of pneumoconiosis for younger miners with less cumulative exposure. In a study done on underground coal miners from 2005 to 2009, when compared to 12 other states, miners in Kentucky, Virginia, and West Virginia, had a greater risk of advanced CWP (RR = 8.1), progressive massive fibrosis (RR = 10.5), and r‐type opacities(RR = 7.7), in younger miners with less mining tenure [Laney et al, ].…”
Section: Introductionmentioning
confidence: 99%